Design principles of the gamified e-assessment for low achievers in introductory programming / Mahfudzah Othman ... [et al.] - Othman, Mahfudzah; Osman, Aznoora; Ahmad, Siti Zulaiha; Abdullah@Dolah, Natrah (UiTM Cawangan Perlis, 2025)
Designing a gamified e-assessment that tailored to the learning requirements of low-achieving students in introductory programming always remains a challenge. By focusing on the integration of gamification and assessment design principles in e-learning platforms for learning programming, this study uses a comparative analysis approach that comprises of three main phases, i) literature search, ii) elicitation and filtration, and iii) review, analysis and extraction of the design principles. Through this qualitative approach, the gamification principles such as the achievement, progression and rules and challenges have been extracted together with the elements of levels, points, badges, progress bars, and leader board. The assessment principles have also been derived consisting of the assessment structure and assessment composition with sub principles of problem-based instructional strategy, formative assessment, post-test strategy, assessment levels, and feedback strategy. The proposed design principles have also been demonstrated through the application in the gamified e-assessment module in an e-learning system.